Factors affecting the underwater phase of the swimming start - Tor, E. (Victoria University, 2015)
The start in swimming is crucial to performance in competition. Following the introduction of the Omega OSB11 block in 2010 saw the evolution of the kick-start, a number of studies have demonstrated that this technique is advantageous to start performance due to the increase in horizontal take-off velocity. Consequently, swimmers are now utilising this technique during competition and this evolution in technique has highlighted the need to re-evaluate swimming start literature. The swimming start is typically broken into three phases; on-block, flight and underwater, with swimmers spending the longest amount of time in the underwater phase. The overall aim of this thesis was to investigate the main factors that affect the underwater phase of the swimming start. To achieve this, the thesis was broken into four sections; the first section characterised the elite swimming start using the kick-start technique and identified key parameters that affect overall start performance. The second section compared three underwater trajectories used by elite swimmers and found that the fastest trajectory is a trade-off between utilising a depth that would reduce resistance while not introducing excessive vertical translation. The third section investigated the relationship between drag, velocity and depth and how it affects the underwater phase. Using the findings from the first three sections theoretical recommendations were established for the ideal underwater trajectory that elite swimmers should adopt to reduce resistance and achieve better start performances. These recommendations were then implemented in the fourth section which aimed to determine if precise quantitative biomechanical feedback could be used to train swimmers to their ideal underwater trajectory. The outcomes of this research highlight the value of a multidisciplinary approach and provide recommendations which can be used practically by coaches and sport scientists in the future to effectively improve start performances.